An Eulerian CFD model and X-ray radiography for coupled nozzle flow and spray in internal combustion engines. (April 2015) - Xue, Q.; Battistoni, M.; Powell, C.F.; Longman, D.E.; Quan, S.P.; Pomraning, E.; Senecal, P.K.; Schmidt, D.P.; Som, S.
Highlights: Implemented an Eulerian model for near-nozzle dense spray. Performed coupled 3-D injector flow and spray simulations with needle motion. Validated the Eulerian model quantitatively with X-ray radiography data. Near-nozzle dense spray was better predicted by Eulerian model than LE model. Abstract: This paper implements a coupled approach to integrate the internal nozzle flow and the ensuing fuel spray using a Volume-of-Fluid (VOF) method in the finite-volume framework. A VOF method is used to model the internal nozzle two-phase flow with a cavitation description closed by the homogeneous relaxation model of Bilicki and Kestin (1990). An Eulerian single velocity field approach by Vallet et al. (2001) is implemented for near-nozzle spray modeling. This Eulerian approach considers the liquid and gas phases as a complex mixture with a highly variable density to describe near nozzle dense sprays. The liquid mass fraction is transported with a model for the turbulent liquid diffusion flux into the gas. Fully-coupled nozzle flow and spray simulations are performed in three dimensions and validated against the X-ray radiography measurements of Kastengren et al. (2014) for a diesel fuel surrogate. A standard k – ∊ Reynolds Averaged Navier Stokes based turbulence model is used in this study and the influence of model constants is evaluated. First, the grid convergence study is performed. The effect of grid size is also evaluated by comparing the fuel distribution against experimental data. Finally, the fuel distribution predicted by the coupled Eulerian approach is compared against that by Lagrangian–Eulerian spray model along with experimental data. The coupled Eulerian approach provides a unique way of coupling the nozzle flow and sprays so that the effects of in-nozzle flow can be directly realized on the fuel spray. Both experiment and numerical simulations show non-cavitation occurring for this injector with convergent nozzle geometry. The study shows that the Eulerian approach has advantages over near-field dense spray distributions.